Increased expression of apolipoprotein E in transgenic rabbits results in reduced levels of very low density lipoproteins and an accumulation of low density lipoproteins in plasma. - Fan, J (1998)
Transgenic rabbits expressing human apo E3 were generated to investigate mechanisms by which apo E modulates plasma lipoprotein metabolism. Compared with nontransgenic littermates expressing approximately 3 mg/dl of endogenous rabbit apo E, male transgenic rabbits expressing approximately 13 mg/dl of human apo E had a 35% decrease in total plasma triglycerides that was due to a reduction in VLDL levels and an absence of large VLDL. With its greater content of apo E, transgenic VLDL had an increased binding affinity for the LDL receptor in vitro, and injected chylomicrons were cleared more rapidly by the liver in transgenic rabbits. In contrast to triglyceride changes, transgenic rabbits had a 70% increase in plasma cholesterol levels due to an accumulation of LDL and apo E-rich HDL. Transgenic and control LDL had the same binding affinity for the LDL receptor. Both transgenic and control rabbits had similar LDL receptor levels, but intravenously injected human LDL were cleared more slowly in transgenic rabbits than in controls. Changes in lipoprotein lipolysis did not contribute to the accumulation of LDL or the reduction in VLDL levels. These observations suggest that the increased content of apo E3 on triglyceride-rich remnant lipoproteins in transgenic rabbits confers a greater affinity for cell surface receptors, thereby increasing remnant clearance from plasma. The apo E-rich large remnants appear to compete more effectively than LDL for receptor-mediated binding and clearance, resulting in delayed clearance and the accumulation of LDL in plasma.